Reflections on Neuro - Law - Ariano, Chiara (2017)
The relationship between law and neuroscience has led to great social concern in recent years. And this we call neurolaw and its implications in criminal cases has been shown in Italy where the law has been practiced.Despite some resistance in the reliability ofthese techniques in the field of courts in Italy, the same does not apply, for example, in America, where neurosciences have a significant influence on legal practice, to the extent that some jurists consider a new formulation of the current parameters of accountability, fraud and guilt as contemporary science would reveal how human behavior is actually the result of a biological determinism, rather than a freewill.